Persepsi Guru Smp Tentang Pelaksanaan Uji Kompetensi Guru (Ukg) 2015 Di Kabupaten Karanganyar - Fahrurrohman, Atriyanto (2016)
Teacher Competency Test is government program to pedagogic competency mapping and professional engaging various instance in centre government environment and region government. The purpose of this study are to describe implementation teachers competency test 2015, to describe perception of junior high school teachers, and reveal teachers expectation of implementation teachers competency test in Karanganyar. This study is descriptive qualitative based on qualitative and case studies. Data collection techniques using observation, interview, documentation, and questionnaire. Result of questionnaire obtain 55 teachers with random sampling techniques are 2 state junior high school in subdistrict of Gondangrejo, interview with teachers as already following UKG. The result showed there are: government as already giving socialization about implementation of UKG (36 or 65,5%). Location of UKG have satisfactoriness laboratory (54 or 98,2%). Schedule of UKG annoy student's study (31 or 56,4%). Teachers are dissatisfied about result of UKG (50 or 90,9%). The conclusion are implementation of UKG 2015 is fairy well. But, there is several attention are schedule of impelemetation of UKG, follow up of result's UKG, language of question and inexpediency between question and answer.